Bisphenol A effects in transthyretin and barrier integrity markers in the choroid plexus: implications in amyloid beta catabolism - Duarte, Ana Catarina Abreu (2014)
The choroid plexus is a multifunctional tissue responsible for a wide range of homeostatic functions crucial to the central nervous system, including secretion of cerebrospinal fluid, synthesis and secretion of important peptides and regulation of the chemical substances exchange between the blood and the cerebrospinal fluid, through the blood-cerebrospinal fluid barrier. Transthyretin, a protein highly expressed and secreted by choroid plexus to the cerebrospinal fluid, is the major amyloid-beta scavenger protein, contributing to its clearance. Sex hormones, as estrogens, upregulate transthyretin expression in choroid plexus, and as a consequence its regulation may be disrupted by substances that interfere with various cellular pathways regulated by endogenous hormones, known as endocrine disruptors chemicals. The human population is exposed to many chemicals with such properties, such as bisphenol A. Therefore, the present study analysed the effects of the endocrine disruptor bisphenol A on transthyretin expression in newborn rats by Whole-Mount fluorescent staining and Western blot, and at the mRNA level by Real time RT-PCR. Moreover, the effects of beta-amyloid on transthyretin expression were also investigated using the same techniques in choroid explants of newborn and young rats. Blood-cerebrospinal fluid barrier plays an important role in the regulation of molecules movement between choroid plexus and cerebrospinal fluid, and it disruption can happen when choroid plexus functions are impaired. Thus, one purpose of this work was determine the effects of both compounds, beta-amyloid and bisphenol A, in bloodcerebrospinal fluid barrier integrity through the evaluation of some membrane protein levels present in this barrier, namely, occludin, E-cadherin, claudin-1 and zonula occludens-1. Beta-amyloid treatment in rat choroid plexus seems to trigger transthyretin upregulation, in a dose-response manner. Transthyretin mRNA levels in newborn rat choroid plexus explants increased much more than in young explants. Increased transthyretin expression levels were not correlated with secretion levels. Additionally, beta-amyloid at 1ug/mL increased reactive oxygen species production in choroid plexus. Low doses of bisphenol A affected transthyretin expression in rat choroid plexus in a non-monotonic dose response way, accordingly to data previously reported in other studies with bisphenol A. The same response profile was observed in transthyretin protein and mRNA levels measured, with higher transthyretin levels verified at 50nM of bisphenol A. As reported before with beta-amyloid treatment, also bisphenol A lead to an increase of transthyretin expression in choroid plexus cells, which was not altered with significance the secretion levels of this protein. Beta-amyloid and bisphenol A clearly influence transthyretin expression in rat choroid plexus, in a dose-response manner, and in a non-monotonic dose response, respectively. In accordance to previous reports, increasing beta-amyloid levels induced transthyretin upregulation. Increased transthyretin production by choroid plexus seems to be a protective mechanisms to avoid beta-amyloid fibrillization and consequent toxicity. Bisphenol A interfered with transthyretin expression, in both positive and negative ways. Therefore, bisphenol A levels might lead to up or down of transthyretin regulation, and consequently, leading to impairment of beta-amyloid levels in brain. Blood-cerebrospinal fluid barrier integrity might be compromised by beta-amyloid and bisphenol A injuries, which explains alteration in secretion rates of controls for treated choroid plexus explants. However, further investigation is required to analyse evolution of transthyretin expression by choroid plexus throughout life, and would be also important evaluate bisphenol A effects in blood-cerebrospinal fluid barrier protein levels, to better understand bisphenol A consequences in beta-amyloid clearance.